2003
DOI: 10.1111/j.1365-2621.2003.tb14129.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk‐based Gels Made with κ‐Carrageenan

Abstract: The gel strength ofÿ k-carrageenan (0.1 to 0.4% w/w) -reconstituted skim milk (2.5 to 20% w/w milk solids) mixtures was influenced by the concentrations of milk solids,ÿ k-carrageenan and cations. Particle size measurements showed that particle interactions in diluted skim milk-k-carrageenan mixtures were dependent on the conformation of theÿk-carrageenan. Heat treatment of milk, resulting in alteration of the casein micelle, did not affect the interaction of k-carrageenan with casein in dilute solutions or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 18 publications
(10 reference statements)
3
17
0
Order By: Relevance
“…2. Storage modulus G 0 increased with both carrageenan and casein concentration; this corresponds with observation by Hemar et al (2002) and Puvanenthiran et al (2002Puvanenthiran et al ( , 2003. For some different carrageenan concentrations (0.1-0.4% w/w) this dependence is quadratic.…”
Section: Rheological Measurementsupporting
confidence: 74%
See 1 more Smart Citation
“…2. Storage modulus G 0 increased with both carrageenan and casein concentration; this corresponds with observation by Hemar et al (2002) and Puvanenthiran et al (2002Puvanenthiran et al ( , 2003. For some different carrageenan concentrations (0.1-0.4% w/w) this dependence is quadratic.…”
Section: Rheological Measurementsupporting
confidence: 74%
“…The presence of milk solids results in a more rigid gel (Hemar, Hall, Munro, & Singh, 2002;Puvanenthiran, Goddard, & Augustin, 2002;Puvanenthiran, Goddard, McKinnon, & Augustin, 2003). Puvanenthiran et al (2002) reported that gelsetting temperature is dependent only on ion concentration (K + , Na + , Ca 2+ ) and is independent on concentration of milk proteins.…”
Section: Introductionmentioning
confidence: 98%
“…Unlike agar, carrageenan has high milk specificity (Towle, 1973). It interacts with the casein micelles under specific conditions of temperature, ionic strength and concentration (Hemar, Hall, Munro, & Singh, 2002;Puvanenthiran, Goddard, McKinnon, & Augustin, 2003), despite the fact that both k-carrageenan and casein micelles are negatively charged at the natural pH of milk (Snoeren et al, 1975). Increases in the diameters of casein micelles in the presence of k-carrageenan have been interpreted as being a result of the binding of the polysaccharide to the micelles (Spagnuolo, Dalgleish, Goff, & Morris, 2005), and direct evidence for the formation of micelle/polysaccharide networks has been demonstrated by electron microscopy (Martin, Goff, Smith, & Dalgleish, 2006;Spagnuolo et al, 2005).…”
Section: Carrageenan Interactions With Casein Micellesmentioning
confidence: 97%
“…However, the most important synergistic interactions of κ-carrageenan as a gelling agent is observed in milk gels where it interacts with milk proteins particularly casein (Puvanenthiran et al 2003;Shchipunov and Chesnokov 2003). Also interactions between κ-carrageenan, milk proteins and modified starch in sterilised dairy desserts have been studied, wherein modified starch imparts a large influence on the complex modulus of the gel (Verbeken et al 2006).…”
Section: Role Of Junction Zones In Gellingmentioning
confidence: 99%
“…Carrageenan is a hydrocolloid that finds maximum application in dairy desserts like puddings, milk shakes, ice cream and chocolate milk because of its ability to form gels in milk at much lower concentrations compared to any other gelling agent (Puvanenthiran et al 2003;de Vries 2004;Verbeken et al 2004). Kappa carageenans form gels in milk at much lower concentrations because of the electrostatic interaction between positively charged region of κ-casein and negatively charged sulphate group of κ-carrageenan that results in increased milk reactivity (Snoeren et al 1975).…”
Section: Applications Of Hydrocolloids As Gelling Agentsmentioning
confidence: 99%